Hyperprogressive Disease in Anorectal Melanoma Treated by PD-1 Inhibitors - Faure, Marjorie; Rochigneux, Philippe; Olive, Daniel; Taix, Sébastien; Brenot-Rossi, Isabelle; Gilabert, Marine (Frontiers in Immunology, 2018)
The 5-year survival rate of primary anorectal malignant melanoma is less than 20%. Optimal treatment of this condition remains controversial regarding locally disease, and whether any preferential survival benefit arises from either abdominoperineal resection or wide local excision remains unknown. The majority of patients progress to metastatic disease, and for decades, the use of chemotherapies such as platines or dacarbazine has been advocated to improve overall survival. The therapeutic use of new checkpoint inhibitors in a variety of trials has provided evidence for an antitumoral effect of PD-1 and/or CTL4 inhibitors in mucosal melanomas, but these treatments must still be further evaluated. Some anecdotal occurrences of rapid progression (i.e., hyperprogressive disease or HPD) while using these immune agents have been described, suggesting potentially deleterious effects of these drugs for some patients. We report a 77-year-old male metastatic anorectal melanoma patient presenting with HPD over 2 months of a PD1 inhibitor treatment course and document this HPD blood phenotype.